2016
DOI: 10.1126/scisignal.aad9256
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial adaptor molecule TSAd is required for VEGF-induced angiogenic sprouting through junctional c-Src activation

Abstract: Activation of vascular endothelial growth factor (VEGF) receptor 2 (VEGFR2) by VEGF binding is critical for vascular morphogenesis. In addition, VEGF disrupts the endothelial barrier by triggering the phosphorylation and turnover of the junctional molecule VE-cadherin, a process mediated by the VEGFR2 downstream effectors T cell-specific adaptor (TSAd) and the tyrosine kinase c-Src. We investigated whether the VEGFR2-TSAd-c-Src pathway was required for angiogenic sprouting. Indeed, Tsad-deficient embryoid bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…During blood vessel formation, the importance of differential adhesion between ECs in the growing sprout has been described from studies in mouse and zebrafish (Bentley et al, 2014;Lenard et al, 2013). Differential cell-cell adhesion is modulated by the junctional localization of the main endothelial adhesion molecule vascular endothelial cadherin (VE-cadherin), the internalization of which is dependent on phosphorylation at distinct tyrosine sites within its intracellular tail (Gordon et al, 2016;Orsenigo et al, 2012;Wessel et al, 2014). In quiescent cell monolayers or ex vivo models, VE-cadherin is neither phosphorylated nor internalized, leading to excessively strong cell-cell adhesions, thereby inhibiting EC migration and sprout formation (Bentley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During blood vessel formation, the importance of differential adhesion between ECs in the growing sprout has been described from studies in mouse and zebrafish (Bentley et al, 2014;Lenard et al, 2013). Differential cell-cell adhesion is modulated by the junctional localization of the main endothelial adhesion molecule vascular endothelial cadherin (VE-cadherin), the internalization of which is dependent on phosphorylation at distinct tyrosine sites within its intracellular tail (Gordon et al, 2016;Orsenigo et al, 2012;Wessel et al, 2014). In quiescent cell monolayers or ex vivo models, VE-cadherin is neither phosphorylated nor internalized, leading to excessively strong cell-cell adhesions, thereby inhibiting EC migration and sprout formation (Bentley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to controlling vascular permeability, VEGFR2-949/TSAd/c-Src/VEcadherin signaling is crucial for sprouting angiogenesis in certain tissues. The presence of TSAd/c-Src at cell-cell junctions, accompanied by VEcadherin phosphorylation and internalization, is required for sprouts to elongate in the trachea (Gordon et al, 2016). Thus, it is known that c-Src exists at junctions (Orsenigo et al, 2012), yet a second subcellular pool has also been identified at focal adhesions (FAs) (Westhoff et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both sprouting and migration were impaired in Casp-8 ECko mice, and as Casp-8 has been shown to regulate the stability of cell junctions in the epidermis (40), we analyzed the distribution of VE-cadherin in vivo in the sprouting front and in the plexus of the growing vasculature of P6 retinas. By using an established image software analysis and classification key (35,41), we distinguished between remodeling ('active') and stable ('inhibited') VE-cadherin patches. As expected, Casp-8 WT retinas presented a highly active VE-cadherin pattern in the sprouting front that was only slightly affected in Casp-8 ECko pups (Suppl Fig.…”
Section: Loss Of Casp-8 Affects the Organization Of Adherens And Tighmentioning
confidence: 99%
“…VEGFR2 signaling is also activated through non-ligand processes, such as shear stress and stretch, that stimulate non-canonical signaling through cytoplasmic tyrosine kinases (e.g. c-Src) (1,2). Multiple mechanisms regulate VEGFRs, including protein expression, ligand availability, co-activators, intracellular tyrosine kinases/phosphatases, intracellular degradation and recycling and cross-talk between VEGFs and VEGFR subtypes (1).…”
Section: A Primer In Vascular Biology and Signaling Of Vegfmentioning
confidence: 99%